Progression of HIV Disease Among Patients on ART in Ethiopia: Application of Longitudinal Count Models - Andualem, Belay Desyebelew; Ayele, Birhanu Teshome (Frontiers in Public Health, 2020)
Although the world is ﬁghting HIV disease in unity and patients are getting antiretroviral therapy3 treatment, HIV disease continues to be a serious health issue for some parts of the world. Large4 number of AIDS related deaths and co-morbidities are being registered every year in resource5 limited countries like Ethiopia. Most studies that have assessed the progression of the disease6 used models that require continuous response. The main objective of this study was to make7 use of appropriate statistical models to analyze routinely collected HIV data and identify risk8 factors associated with progression of CD4+ cell count of patients under ART treatment in Debre9 Markos Referral Hospital, Ethiopia. In this longitudinal retrospective study, routinely data of 44510 HIV patients registered for ART treatment in the Hospital was used. As overdispersion was11 detected in the data, Poisson-Gamma, Poisson-Normal, and Poisson-Gamma-Normal models12 were applied to account for overdispersion and correlation in the data. Poisson-Gamma-Normal13 model with random intercept was selected as the best model to ﬁt the data. The ﬁndings of the14 study revealed time on treatment, sex of patients, baseline WHO stage and baseline CD4+ cell15 count as signiﬁcant factors for progression of CD4+ cell count.